Avoiding the elephant in the room: echo chambers and the (de-)politicization of COVID-19 during the 2021 German federal election on Twitter - Jasmin Riedl; Wiebke Drews; Friederike Richter (Frontiers in Political Science)
During the 2021 German federal election campaign, COVID-19 emerged as a highly salient issue in public discourse. Despite its significance, most political parties adopted a strategy of depoliticization, likely as a means to mitigate potential electoral losses. Against this backdrop, our paper examines whether and to what extent COVID-19 was discussed on Twitter in the run-up to the election. Our analysis draws on two original datasets collected in the four weeks preceding the election on September 26, 2021: one comprising 7,374,166 German-language posts mentioning the federal election and another with 3,195,198 German-language posts commenting on the COVID-19 pandemic. Using these datasets, we calculated echo chamber scores (ECS) based on ideological leanings within retweet-based networks and examined the politicization of COVID-19 in the digital election campaign. Our findings reveal that the online discourse polarized into two distinct echo chambers: a “safety-first” community advocating for strict COVID-19 measures, and a “freedom-first” community opposing such measures. While most political figures sought to depoliticize the issue online, key political actors – due to their leadership roles in the upcoming election-could neither avoid addressing the pandemic nor being publicly addressed on the matter. In particular, users within the echo chambers focused attention on two key health policy leaders from opposing political camps: Jens Spahn, the then-incumbent Health Minister from the Christian Democratic Unio/Christian Social Union (CDU/CSU), and Karl Lauterbach from the Social Democratic Party (SPD), who would later become health minister. Our results underscore that, despite efforts to minimize the salience of COVID-19 in the lead-up to the election, certain leaders were compelled to confront the “elephant in the room” due to the demands of their roles during the health crisis.